2017
DOI: 10.1021/acs.nanolett.6b05068
|View full text |Cite
|
Sign up to set email alerts
|

Probing Homogeneous Line Broadening in CdSe Nanocrystals Using Multidimensional Electronic Spectroscopy

Abstract: The finite spectral line width of an ensemble of CdSe nanocrystals arises from size and shape inhomogeneity and the single-nanocrystal spectrum itself. This line width directly limits the performance of nanocrystal-based devices, yet most optical measurements cannot resolve the underlying contributions. We use two-dimensional electronic spectroscopy (2D ES) to measure the line width of the band-edge exciton of CdSe nanocrystals as a function of radii and surface chemistry. We find that the homogeneous width de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(136 citation statements)
references
References 70 publications
12
121
3
Order By: Relevance
“…Intensity (a.u.) (a) The obtained 2D spectra of CdSe/ZnS NCs are consistent with literature results characterized by established approaches [58,59]. The two diagonal peaks correspond to the two excitonic transitions (i.e., 1S 1/2 (e) -1S 3/2 (h) and 1S 1/2 (e) -2S 3/2 (h)) sharing a common excited level in the conduction band [60].…”
Section: Signal Recovery and Noise Suppressionsupporting
confidence: 88%
See 1 more Smart Citation
“…Intensity (a.u.) (a) The obtained 2D spectra of CdSe/ZnS NCs are consistent with literature results characterized by established approaches [58,59]. The two diagonal peaks correspond to the two excitonic transitions (i.e., 1S 1/2 (e) -1S 3/2 (h) and 1S 1/2 (e) -2S 3/2 (h)) sharing a common excited level in the conduction band [60].…”
Section: Signal Recovery and Noise Suppressionsupporting
confidence: 88%
“…The 2D spectra are recorded as a function of waiting time (T) (see Visualization 1). The signals exhibit oscillations along T due to strong vibrational couplings [58,59]. Phase retrieval is indispensable for 2DES.…”
Section: Signal Recovery and Noise Suppressionmentioning
confidence: 99%
“…However, as seen in Figures 4 and 5 in Ref. [55] and in Figures 3 and S5 of Ref. [56], peaks do appear in beating maps at spacings other than the selected ω 2 value.…”
Section: Theory: 2d Es Simulationsmentioning
confidence: 77%
“…Turner and co-workersm easured the 2DES spectra of CdSe QDs to characterize the homogeneous line broadening of the band-edge exciton peak (X 1 )a safunction of size from ar adius of 1.4 to 3.0 nm. [64] They measuredt hat the homogeneous linewidth narrows with increasings ize. They also observed that the 2DES spectra do not change with T from 75 fs to 900 ps.…”
Section: Cdse Nanomaterialsmentioning
confidence: 99%
“…Although it may be non‐trivial to quantitatively measure the FFCF of the excitonic transitions of CdSe QDs, it is still possible to qualitatively characterize the spectral diffusion dynamics. Turner and co‐workers measured the 2DES spectra of CdSe QDs to characterize the homogeneous line broadening of the band‐edge exciton peak (X 1 ) as a function of size from a radius of 1.4 to 3.0 nm . They measured that the homogeneous linewidth narrows with increasing size.…”
Section: Experimental Measurements Of Spectral Diffusionmentioning
confidence: 99%